Impact of school-based and out-of-school mental health services on reducing school absence and school suspension among children with psychiatric disorders. (April 2018) - Kang-Yi, Christina D.; Wolk, Courtney Benjamin; Locke, Jill; Beidas, Rinad S.; Lareef, Ishara; Pisciella, Aelesia E.; Lim, Suet; Evans, Arthur C.; Mandell, David S.
Highlights: Objective: Examined impact of school-mental health service use on academic outcomes. Study Sample: 755 children who were enrolled in 1st through 8th grades. Methods: Longitudinal multi-level analysis of children's academic outcomes. Results: Positive impact of school-mental health service use on school suspension. Conclusion: Mental health program tailored to school setting is important.